Australia Europe Security and Defence Cooperation in the Twenty First Century: Challenges and Opportunities - Muraviev, Alexey (Australian Scholarly Publishing, 2018)
This book on the Australia - European Union relationship comes at an opportune time. While it was a case of 'So distant ...' it is now one where it can be 'So close'.